2015
DOI: 10.1002/dev.21375
|View full text |Cite
|
Sign up to set email alerts
|

Visual selective attention biases contribute to the other‐race effect among 9‐month‐old infants

Abstract: During the first year of life, infants maintain their ability to discriminate faces from their own race but become less able to differentiate other-race faces. Though this is likely due to daily experience with own-race faces, the mechanisms linking repeated exposure to optimal face processing remain unclear. One possibility is that frequent experience with own-race faces generates a selective attention bias to these faces. Selective attention elicits enhancement of attended information and suppression of dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 68 publications
(41 citation statements)
references
References 63 publications
8
33
0
Order By: Relevance
“…For example, Caucasian adults’ recognition of unfamiliar Black faces can be enhanced by cueing their attention to regions high diagnostic values (Hills & Lewis, ). Similarly, Markant, Oakes, and Amso () found that Caucasian infants could be biased to discriminate between individual Caucasian or individual African American faces by manipulating them to attend to faces of one race versus the other; in this paradigm, Caucasian infants showed superior discrimination for the face race that they attended, and not necessarily the familiar own‐race, Caucasian faces. It is possible that differences in the kinds of faces infants encounter every day (i.e., their community face experience) cause them to engage their attention differently when shown own‐ versus other‐race faces, and as a result they process and learn differently about those faces.…”
Section: Discussionmentioning
confidence: 96%
“…For example, Caucasian adults’ recognition of unfamiliar Black faces can be enhanced by cueing their attention to regions high diagnostic values (Hills & Lewis, ). Similarly, Markant, Oakes, and Amso () found that Caucasian infants could be biased to discriminate between individual Caucasian or individual African American faces by manipulating them to attend to faces of one race versus the other; in this paradigm, Caucasian infants showed superior discrimination for the face race that they attended, and not necessarily the familiar own‐race, Caucasian faces. It is possible that differences in the kinds of faces infants encounter every day (i.e., their community face experience) cause them to engage their attention differently when shown own‐ versus other‐race faces, and as a result they process and learn differently about those faces.…”
Section: Discussionmentioning
confidence: 96%
“…The visual processing of attended information can be improved by manipulating one's selective attention (Markant et al, ). This heightened processing not only includes improved quality of vision, but enhanced acuity and contrast sensitivity to the selected stimuli (Carrasco, ), enhancing the encoding and recognition of the attended stimuli, relative to the unattended stimuli (Rutman, Clapp, Chadick, & Gazzaley, ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the finding of the validity effect in the ventral temporal regions in addition to the occipital ROIs suggests that shifting attention to a valid location enhances not only visual processing of basic information (e.g., color, brightness) but also high-level visual processing (e.g., object identification). Recent studies have highlighted the interactions between infant spatial attention and social perception of faces (Hayden, Bhatt, Kangas, Zieber, & Joseph, 2012; Markant et al, 2015), eye gaze (Farroni et al, 2004; Reid, Striano, Kaufman, & Johnson, 2004), and human biomechanical motion (Daum & Gredeback, 2011, Rohlfing, Longo, & Bertenthal, 2012). For instance, Daum and Gredeback (2011) investigated how the observed goal-directed manual grasping actions modulated the infants’ spatial attention in a modified spatial cueing paradigm.…”
Section: Discussionmentioning
confidence: 99%
“…The cue was presented for 300 ms and then turned off. The central stimulus was frozen when the cue was presented in order to reduce the possibility of infants moving their eyes toward the cue before the target onset (e.g., Richards, 2005; Markant, Oakes, & Amso, 2015). After the cue was turned off, the fixation stimulus was left on the screen for 150 ms in the short SOA condition and 1050 ms in the long SOA condition.…”
Section: Methodsmentioning
confidence: 99%